PENGAMBILAN KEPUTUSAN DITINJAU DARI MANAJEMEN DIRI DAN KEMATANGAN EMOSI - Satar, Muhammad; Yusri, Nur Aisyiah (Al-Qalb : Jurnal Psikologi Islam, 2019)
The orientation of decision making is actually supported also by one’s experience, while attitudes toward experience itself are related to one’s emotional maturity. Emotional maturity is a valuable capital. People who have more mature emotions will be able to choose what is best and what they must avoid. The emotional maturity of an employee can be seen from the way he faces challenges, how his responsibilities towards work, and how his life views the world, so that the difficulties faced in making a decision will be lighter than employees who have lower emotional maturity. Emotional maturity is characterized by how conflicts are solved, and how difficulties are handled. People who are adults, in this case are emotionally mature, see their difficulties not as catastrophe, but as challenges, so that when he is faced with a situation where he has to choose an alternative offered to him, armed with the knowledge and experience he has it will be easier to make decisions that are considered most appropriate. He is willing to take risks, but still based on the most appropriate estimates that can be obtained.